Kendali Mobil Robot menggunakan Isyarat Tangan Berbasis Arduino - Jati Widyo Leksono; Agung Samudra; Nanndo Yannuansa; Ahmad Fauzi (Electro Luceat, 2020)
The development of technology robot car from year to year, it turned out continue to experienced the level of rapid progress. Current robots are no longer controlled by using the remote control, but can use command from the man directly. The development of a robot car capable of running in accordance with a hand gesture. Palm of human hand affixed to a sensor that is able to read movement direction of top, bottom, left side and right side. Sensor readings from the gesture of the hand, module sends data to the receiver that are contained in the robot wirelessly. Robot will receive data input control command logic programming to specify the action. The robot will move forward, backward, turn right, turn left, stop. Control hand gesture that is using the sensor module MPU-6050 are transmitted through radio frequency waves NRF24L01. Based on the results of testing, module proficiency level sensor capable of reading the position of a point of the axis x, y, and z. The results of response speed of sensor against car is able to connect quickly 0.45 s. Testing the average speed of car robot is capable of driving amounted to 3.496,50 rpm up to 4.596,50 rpm.